LSCO/SCO OʻTA PANJARA OʻTA OʻTKAZUVCHANLIK KRITIK HARORATI HAQIDA - Otajonov, S.M.; Ya.Yavidov, B. (SCIENCE and SOCIETY, 2024)
In this paper, the superlattice superconductivity of La2-xSrxCuO4/Sm2CuO4 has been theoretically considered. Our theoretical approach is based on the extended Holstein model and the bipolaron model of superconductivity. In particular, the dependence of the La1.85Sr0.15CuO4/Sm2CuO4 superlattice superconducting critical temperature Tc on the thickness (df) of the La1.85Sr0.15CuO4 film in the superlattice or the number of La1.85Sr0.15CuO4 half-layers Nstc.p in the superlattice was studied. Based on the principle of Bose-Einstein condensation of two-node bipolaron gas in La1.85Sr0.15CuO4, it was shown that it is possible to explain the dependence of critical temperature Tc on the La1.85Sr0.15CuO4 film thickness (df) in the superlattice or the number of La1.85Sr0.15CuO4 half-layers Nstc.p in the superlattice.
Keywords: cuprates; superlattice; films; film thickness; bipolaron; superconductivity; Bose-Einstein condensation